2021
DOI: 10.1126/sciimmunol.abi6950
|View full text |Cite
|
Sign up to set email alerts
|

Distinct antibody and memory B cell responses in SARS-CoV-2 naïve and recovered individuals after mRNA vaccination

Abstract: Novel mRNA vaccines for SARS-CoV-2 have been authorized for emergency use. Despite their efficacy in clinical trials, data on mRNA vaccine-induced immune responses are mostly limited to serological analyses. Here, we interrogated antibody and antigen-specific memory B cells over time in 33 SARS-CoV-2 naïve and 11 SARS-CoV-2 recovered subjects. SARS-CoV-2 naïve individuals required both vaccine doses for optimal increases in antibodies, particularly for neutralizing titers against the B.1.351 variant. Memory B … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

110
564
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 613 publications
(716 citation statements)
references
References 56 publications
110
564
4
3
Order By: Relevance
“…2b). In contrast and consistent with previous reports 5,8,15 , convalescent individuals that received mRNA vaccines showed an average 8.6-fold increase in the number of circulating RBD specific memory B cells (Fig. 2b).…”
Section: Memory B Cellssupporting
confidence: 93%
See 1 more Smart Citation
“…2b). In contrast and consistent with previous reports 5,8,15 , convalescent individuals that received mRNA vaccines showed an average 8.6-fold increase in the number of circulating RBD specific memory B cells (Fig. 2b).…”
Section: Memory B Cellssupporting
confidence: 93%
“…These titers are an order of magnitude higher than the neutralizing titers achieved against the wild-type SARS-CoV-2 at the peak of the initial response in infected individuals and in naïve individuals receiving both doses of mRNA vaccines (Fig. 1d and 2,[5][6][7][8] ).…”
mentioning
confidence: 99%
“…Our study on specific T cells has some limitations: (1) the sample size for which in-depth T-cell profiling was performed was limited to 20 donors; (2) we only focused on S-specific T cells; and (3) we were not able to further address CD8 + T-cell responses to VOC, due to low frequency of SARS-CoV-2-specific CD8 + T cells. Although we hypothesize this was due to minimal disease severity in this HCW cohort (40,41), alternatively this could be because of limited sensitivity when using peptide pools containing overlapping 15mers. Additional studies with smaller peptides (8-10mers) predicted or shown to bind HLA class I are advised to specifically study VOC cross-reactive CD8 + T-cell responses.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we regarded individuals with a SI > 3 as responders, however this was in an intensive care unit (ICU) cohort with strong T-cell responses (11). Since the strength of the Tcell response seems to be correlated to disease severity (40,41), we lowered the arbitrary cut-off to an SI > 2 to identify responders after mild COVID-19 (Table S1). In COVID-19 naive donors, CD4 + T-cell responders were not observed prevaccination, whereas 5 out of 7 responders were identified after 1 or 2 vaccinations.…”
Section: Rapid Boosting Of S-specific T Cells In Covid-19 Recovered Donorsmentioning
confidence: 99%
“…Analogous results were reported in a recent study by Goel et al, demonstrating the amplification of neutralizing titers against D614G and B.1.351 pseudoviruses in individuals with prior infection after a single dose of mRNA vaccine, with little improvement observed after dose two. 5 Notably, Stamatatos et al also show that B.1.351 neutralizing titers in previously infected vaccinees after a single dose were comparable to or higher than autologous neutralizing titers in previously naïve vaccinees after two doses of mRNA vaccine. 3 This result is significant given that the latter is associated with greater than 90% protective efficacy against COVID-19 in clinical trials.…”
mentioning
confidence: 96%